1996
DOI: 10.1073/pnas.93.19.10309
|View full text |Cite
|
Sign up to set email alerts
|

Use of genetic suppressor elements to dissect distinct biological effects of separate p53 domains.

Abstract: ABSTRACTp53 is a multifunctional tumor suppressor protein involved in the negative control of cell growth. Mutations in p53 cause alterations in cellular phenotype, including immortalization, neoplastic transformation, and resistance to DNA-damaging drugs. To help dissect distinct functions of p53, a set of genetic suppressor elements (GSEs) capable of inducing different p53-related phenotypes in rodent embryo fibroblasts was isolated from a retroviral library of random rat p53 cDNA fragments. All the GSEs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
167
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 36 publications
(38 reference statements)
8
167
1
Order By: Relevance
“…We expressed a dominant p53 inhibitor, GSE-22 (ref. 15), in early and later-passage 3% oxygen MEFs and confirmed that it increased p53 levels, as previously reported 15 (see Supplementary Information, Fig. S1a).…”
supporting
confidence: 89%
“…We expressed a dominant p53 inhibitor, GSE-22 (ref. 15), in early and later-passage 3% oxygen MEFs and confirmed that it increased p53 levels, as previously reported 15 (see Supplementary Information, Fig. S1a).…”
supporting
confidence: 89%
“…At 24 h, the population of G 2 /M cells was still predominant, as compared to the proportion of S-phase cells. To determine if p53 activity was required for the radiationinduced cell cycle arrest, C4-2 cells were stably transfected with a C-terminal fragment dominantnegative (DN) p53 mutant (Ossovskaya et al, 1996), such that following irradiation, its transcriptional activity was abrogated, as shown by a dramatic decrease from abundant to undetectable levels of p21 WAF1 (S. Ray et al, unpublished data). Similar to the parental C4-2, the derivative cells containing the stably expressed DNp53 had a robust 4C arrest following irradiation (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…REF52 sublines expressing N-ras asp12 transgene along with either dominant-negative p53 cDNA fragment (GSE22, Genetic Suppressive Element #22 ± Ossovskaya et al, 1996) or mutant R175H p53 (REF52/GSE-ras and REF52/His175-ras cell lines, respectively) were obtained by infection with retroviral vectors carrying the N-ras asp12 cDNA (pPS/hygroras), mutant human p53 cDNA (pPS/neo-p53 175 ) and p53-GSE (pLXSN/GSE22) which were described by us earlier Kopnin et al, 1995;Ossovskaya et al, 1996). Also we used (i) wt-p53-positive Rat-2 sublines bearing human N-ras proto-oncogene or H-ras gene mutated at codon 12 (Rat-2/5 and Rat2-HT1 cell lines, respectively) driven by inducible mouse mammary tumor virus promoter (McKay et al, 1986;Alexandrova et al, 1993), and (ii) human pseudodiploid hereditary non-polyposis colon carcinoma LIM1215 (Whitehead et al, 1985) containing two wtp53 gene alleles (Zaichuk et al, 1993) and its sublines expressing transduced N-ras asp12 oncogene and/or dominantnegative p53 mutants (Agapova et al, 1996;.…”
Section: Cellsmentioning
confidence: 99%